Genomic Insights Into Last-Line Antimicrobial Resistance in Multidrug-Resistant Staphylococcus and Vancomycin-Resistant Enterococcus - Turner, Adrianna M.; Lee, Jean Y. H.; Gorrie, Claire L.; Howden, Benjamin P.; Carter, Glen P. (Frontiers in Microbiology, 2021)
Multidrug-resistant Staphylococcus and vancomycin-resistant Enterococcus (VRE) are important human pathogens that are resistant to most clinical antibiotics. Treatment options are limited and often require the use of ‘last-line’ antimicrobials such as linezolid, daptomycin, and in the case of Staphylococcus, also vancomycin. The emergence of resistance to these last-line antimicrobial agents is therefore of considerable clinical concern. This mini-review provides an overview of resistance to last-line antimicrobial agents in Staphylococcus and VRE, with a particular focus on how genomics has provided critical insights into the emergence of resistant clones, the molecular mechanisms of resistance, and the importance of mobile genetic elements in the global spread of resistance to linezolid.